On local linear estimation in nonparametric errors-in-variables models - Zwanzig, S. (Інститут математики НАН України, 2007)
Local linear methods are applied to a nonparametric regression model with normal errors in the variables and uniform distribution of the variables. The local neighborhood is determined with help of deconvolution kernels. Two different linear estimation method are used: the naive estimator and the total least squares estimator. Both local linear estimators are consistent. But only the local naive estimator delivers an estimation of the tangent.